The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/ten.tea.2011.0276
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Macroporous Polyvinyl Alcohol Scaffold Promotes Chondrocyte Migration and Interface Formation in anIn VitroCartilage Defect Model

Abstract: Scaffold-cartilage integration is critical for the clinical success of a scaffold used for the repair of a focal cartilage defect. In this study, a macroporous polyvinyl alcohol (PVA) scaffold was found to facilitate chondrocyte infiltration and interfacial matrix formation in a juvenile bovine in vitro cartilage defect model. These results were found to depend on the press-fit between the scaffold and the cartilage, pretreatment of the cartilage with collagenase prior to scaffold insertion, and chondrocyte pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 34 publications
1
50
1
Order By: Relevance
“…Some researchers found that the integrative process began with attachment of the isolated chondrocytes onto the integrative interface. 2 The attached chondrocytes could migrate further into the host cartilage as recently reported by Theodoropoulos et al 3 and Ng et al 4 Furthermore, the migrated cells could drive a remodeling of the extracellualr matrix and make the interface to be a tissue continuum. 5 Therefore, chondrocyte migration might be an important contributor to the formation of an integrative interface.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Some researchers found that the integrative process began with attachment of the isolated chondrocytes onto the integrative interface. 2 The attached chondrocytes could migrate further into the host cartilage as recently reported by Theodoropoulos et al 3 and Ng et al 4 Furthermore, the migrated cells could drive a remodeling of the extracellualr matrix and make the interface to be a tissue continuum. 5 Therefore, chondrocyte migration might be an important contributor to the formation of an integrative interface.…”
Section: Introductionmentioning
confidence: 70%
“…Ng et al 4 found that the polyvinyl alcohol scaffold could promote chondrocyte migration and interface formation in an in vitro cartilage defect model. Thus, chondrocyte migration can be accelerated by altering the extracellular environment, but chondrocyte migration is also regulated by a network of intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…64 Such scaffolds contain complex ECM components mimicking with 65 the ECM of the native tissue, and exhibit attractive bioactivity for 66 tissue remodeling and regeneration [12][13][14]. The decellularization 67 technique can remove cellular membrane antigens and nuclear 68 components to minimize the immune response, allowing the 69 material to be used safely in clinics. For example, decellularized 70 porcine small intestinal submucosa (SIS) material has been com- 71 mercialized and clinically used for skeletal muscle treatment 72 [15].…”
mentioning
confidence: 99%
“…S4G). It 605 was reported that the chondrocytes could migrate from native car-606 tilage to implanted adjacent scaffolds in vivo and maintain typical 607 chondrocyte-like morphology [66,67]. 608 The good injectability of the meniscus-derived hydrogel was 609 verified by injecting the pre-gel solution into the mouse subcuta- …”
mentioning
confidence: 99%
“…More importantly, the foams must be biocompatible with body tissues for biomedical applications such as absorption of serum in eye surgery, making scaffolds for cell growth, and in drug delivery systems. [1][2][3][4][5][6][7][8][9] Various methods for preparation of biomedical foams have been reported including gas foaming of N 2 or CO 2 , overrun process (mechanical mixing of polymer solution at low temperature to entrap air bubbles) 10,11 and using a foaming agent. [12][13][14][15] These techniques are usually associated with polymer cross-linking methods.…”
Section: Introductionmentioning
confidence: 99%